2004
DOI: 10.1093/intimm/dxh038
|View full text |Cite
|
Sign up to set email alerts
|

Allicin stimulates lymphocytes and elicits an antitumor effect: a possible role of p21ras

Abstract: Allicin, the main organic allyl sulfur component in garlic, exhibits immune-stimulatory and antitumor properties. Allicin stimulated [(3)H]thymidine incorporation in mouse splenocytes and enhanced cell-mediated cytotoxicity in human peripheral mononuclear cells. Multiple administration (i.p.) of allicin elicited a marked antitumor effect in mice inoculated with B-16 melanoma and MCA-105 fibrosarcoma. The immune-stimulatory and antitumor effects of allicin are characterized by a bell-shaped curve, i.e. allicin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 40 publications
1
31
0
3
Order By: Relevance
“…This observation is in agreement with the previously reported cytotoxicity of TAM on MCF-7 and MDA-MB-231 human breast cancer cells (Al-Akoum et al, 2007), OC2 human oral cancer cells (Chu et al, 2007), human epidermal keratinocyte cell line (Bhatia et al, 2010), human chronic myeloid leukemia (K562) cell line (Pedroso et al, 2013). Allicin produced a reduction in relative tumor size supporting the well-established antitumor effect of allicin against a variety of tumors in preclinical models (Padilla-Camberos et al, 2010;Patya et al, 2004). It was suggested that the antitumor effect of allicin is related to its immune-stimulatory properties (Patya et al, 2004) and/ or induced apoptosis (Padilla-Camberos et al, 2010).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This observation is in agreement with the previously reported cytotoxicity of TAM on MCF-7 and MDA-MB-231 human breast cancer cells (Al-Akoum et al, 2007), OC2 human oral cancer cells (Chu et al, 2007), human epidermal keratinocyte cell line (Bhatia et al, 2010), human chronic myeloid leukemia (K562) cell line (Pedroso et al, 2013). Allicin produced a reduction in relative tumor size supporting the well-established antitumor effect of allicin against a variety of tumors in preclinical models (Padilla-Camberos et al, 2010;Patya et al, 2004). It was suggested that the antitumor effect of allicin is related to its immune-stimulatory properties (Patya et al, 2004) and/ or induced apoptosis (Padilla-Camberos et al, 2010).…”
Section: Discussionsupporting
confidence: 53%
“…Allicin produced a reduction in relative tumor size supporting the well-established antitumor effect of allicin against a variety of tumors in preclinical models (Padilla-Camberos et al, 2010;Patya et al, 2004). It was suggested that the antitumor effect of allicin is related to its immune-stimulatory properties (Patya et al, 2004) and/ or induced apoptosis (Padilla-Camberos et al, 2010). Combination between TAM and allicin increased the percent inhibition of the growth of solid tumor in mice confirming the synergistic effect between the drugs.…”
Section: Discussionmentioning
confidence: 75%
“…The antimicrobial [8,9], antitumor [10][11][12], antifungal [13], and antigenotoxic [14], activities of allicin have been reported. Meanwhile, various researches have indicated that garlic and allicin have inhibitory immunomodulatory action [15], they modulate immune responses, enhance humoral immunity and minimize immunological stress, and thus affect growth performance most positively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that allicin inhibits the growth of various cancer cells and might play a major role as an anti-cancer agent. Moreover, allicin reduces the risk of cancer development, such as melanoma and leukemia (16,25,26). Therefore, this study evaluated allicin as a potential a new chemotherapeutic agent of GBM.…”
Section: Discussionmentioning
confidence: 99%